The Role of Technology Integration in Public Sector Accounting Fraud Prevention Efforts - Mobilingo, Dea Saufika; Hailah; Nirwana (Jurnal Akuntansi, Manajemen, dan Perencanaan Kebijakan, 2024)
This research aims to determine the role of public-sector accounting information technology in preventing fraud in public-sector organizations. The study was a literature review based on articles suitable for further analysis of the research topic. The study found that there are ways to prevent fraud that, include technology and prevention strategies. The technology strategy includes leveraging data protection officers for fraud prevention, IoT access, data access management, timely reporting, and real-time data management. The prevention strategy is to develop a fraud detection system using machine algorithms, data mining, and meta-learning techniques.